Normalizing HDAC2 Levels in the Spinal Cord Alleviates Thermal and Mechanical Hyperalgesia After Peripheral Nerve Injury and Promotes GAD65 and KCC2 Expression - Ouyang, Bihan; Chen, Dan; Hou, Xinran; Wang, Tongxuan; Wang, Jian; Zou, Wangyuan; Song, Zongbin; Huang, Changsheng; Guo, Qulian; Weng, Yingqi (Frontiers in Neuroscience, 2019)
The neuropathic pain is a worldwide health concern with unsatisfied treatment. Accumulating evidence suggested that histone hypoacetylation is involved in the development and maintenance of neuropathic pain. Thus many natural or synthetic histone deacetylases inhibitors were tested and exhibited a remarkable analgesic effect to neuropathic pain animals. However, limited information was obtained on the specific subtypes of HDACs contributing to neuropathic pain. In this study, by using the chronic constriction injury (CCI) rat model, we found that the mRNA and protein level of HDAC2 was increased in the lumbar spinal cord of rats after sciatic nerve injury. Intrathecal injection of TSA, a pan-HDAC inhibitor, suppressed the augment of HDAC2 protein but not mRNA, and showed dose-dependent pain-relieving effect. By introducing HDAC2-specific shRNA into the spinal cord via lentivirus vector, we confirmed that HDAC2 is a subtype of HDACs mediating the mechanical and thermal hyperalgesia after nerve injury. Further examination found two essential participants in the inhibitory circuit of the central nervous system, GAD65 and KCC2, were increased in the spinal cord of CCI rats after HDAC2 knocking-down. Thus, our research confirmed that the HDAC2 was involved in the mechanical and thermal hyperalgesia induced by peripheral nerve injury, GAD65 and KCC2 were the possible downstream targets of HDAC2 in the pain-modulating pathway.